Posttranslational hydroxylation of ankyrin repeats in IkappaB proteins by the hypoxia-inducible factor (HIF) asparaginyl hydroxylase, factor inhibiting HIF (FIH). - Cockman, M; Lancaster, D; Stolze, I; Hewitson, K; McDonough, M; Coleman, M; Coles, C; Yu, X; Hay, RT; Ley, S; Pugh, C; Oldham, N; et al. (2006)
Studies on hypoxia-sensitive pathways have revealed a series of Fe(II)-dependent dioxygenases that regulate hypoxia-inducible factor (HIF) by prolyl and asparaginyl hydroxylation. The recognition of these unprecedented signaling processes has led to a search for other substrates of the HIF hydroxylases. Here we show that the human HIF asparaginyl hydroxylase, factor inhibiting HIF (FIH), also efficiently hydroxylates specific asparaginyl (Asn)-residues within proteins of the IkappaB family. After the identification of a series of ankyrin repeat domain (ARD)-containing proteins in a screen for proteins interacting with FIH, the ARDs of p105 (NFKB1) and IkappaBalpha were shown to be efficiently hydroxylated by FIH at specific Asn residues in the hairpin loops linking particular ankyrin repeats. The target Asn residue is highly conserved as part of the ankyrin consensus, and peptides derived from a diverse range of ARD-containing proteins supported FIH enzyme activity. These findings demonstrate that this type of protein hydroxylation is not restricted to HIF and strongly suggest that FIH-dependent ARD hydroxylation is a common occurrence, potentially providing an oxygen-sensitive signal to a diverse range of processes.